Pengembangan Kreativitas Sumberdaya Manusia Pelaku Usaha Mikro Kecil Dan Menengah Dinas Koperasi Ukm Tenaga Kerja Dan Transmigrasi - Sugiyanto, Sugiyanto; Musoli, Musoli (Jurnal Bisnis : Teori dan Implementasi, 2017)
Yogyakarta city which divided into 14 districts and 45 sub-districts has the potential of  micro, small and medium business (SMEs)  of 22.091 units with various types of products and services.  In fact, SMEs are the economic actors of micro, small and medium enterprises that have a large role in addressing unemployment and poverty in the city. Since HR MSMEs are the parts of creative economic actors, it is important that HR of MSMEs to develop their creativity skills. Given the MSMEs actors in Yogyakarta have not maximized in the work, therefore, it   needs to maximize their creativity skill. Through creativity improvement in HR MSMEs, they can maintain and development of new ideas in form of new products, new packaging, new marketing models, and increased partnerships/networks that finally become a powerhouse economy competitive.